An Emerging Class of Long Non-coding RNA With Oncogenic Role Arises From the snoRNA Host Genes - Zimta, Alina-Andreea; Tigu, Adrian Bogdan; Braicu, Cornelia; Stefan, Cristina; Ionescu, Calin; Berindan-Neagoe, Ioana (Frontiers in Oncology, 2020)
The small nucleolar RNA host geness (SNHG) consist of a group of long non-coding RNAs, which are reported in many studies as being overexpressed in various cancers. With very few exceptions, the SNHGs (SNHG1, SNHG3, SNHG5, SNHG6, SNHG7, SNHG12, SNHG15, SNHG16, SNHG20) are recognized as inducing increased proliferation, cell cycle progression, invasion and metastasis of cancer cells which makes this class of transcripts a viable biomarker for cancer development and aggressiveness. Through our literature research , we also found silencing of SNHGs through small interfering RNAs or short hairpin RNAs is very effective in both in vitro and in vivo experiments by lowering solid cancers aggressiveness. The knock down of SNHG as a new cancer therapeutic option should be investigated more in the future.